Implementasi Pendidikan Koperasi Di Perguruan Tinggi (Studi Analisis Kopma Iain Kudus) - Hamdan Adib (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
Cooperative education organized by Student Cooperative Units in higher education institutions continuously strives to develop students' knowledge and skills while fostering an understanding of cooperative principles. The growing number of cooperatives in Indonesia highlights the necessity of cooperative education, particularly for university students. This research is a descriptive qualitative study conducted at the Student Cooperative (Kopma) of IAIN Kudus, Central Java. Data were collected through non-participant observation and semi-structured interviews. Data analysis was performed using Miles and Huberman's data reduction, data display, and data verification techniques. The findings of this study indicate that Kopma IAIN Kudus has a structured cooperative education program divided into three levels: Basic Cooperative Education, Intermediate Cooperative Education, and Advanced Cooperative Education. Basic Cooperative Education aims to provide foundational knowledge about the concepts of cooperatives, their history, principles, and members' rights and responsibilities. Intermediate Cooperative Education offers a more in-depth understanding of cooperative management, financial aspects, and leadership skills. Advanced Cooperative Education represents the highest level, encompassing a comprehensive understanding of more complex aspects, including innovation, human resource management, and current issues in the cooperative sector.